PSYCHOLOGICAL MECHANISMS OF DEVELOPING ADOLESCENTS COGNITIVE PROCESSES IN ENGLISH LANGUAGE TEACHING - Dr Dilnoza Kurbonova (American Journals Publishing, 2025)
As language learning is the natural, conscious, and inadvertent learning, it is fully connected with psychological process, that’s to say cognitive skills of the language learners. Through language teaching cognitive skills of the learners can be developed appropriately. This paper highlights the actuality of psychology in developing adolescents’ cognitive skills while teaching English language. As well, psychological mechanisms involved in development of adolescents’ cognitive processes in teaching English languages are given in the paper.
Keywords: Psychology, cognitive process, language teaching, education, learning capacities, mechanisms, teachers’ and students’ roles